An optimization model for selecting the optimal green systems by considering the thermal comfort and energy consumption. (1st May 2016) - Kim, Jimin; Hong, Taehoon; Jeong, Jaemin; Koo, Choongwan; Jeong, Kwangbok
Highlights: An optimization model for selecting the optimal green systems was developed. Thermal comfort, energy, LCC & LCA were used to select the optimal green systems. A total of 27 types of the green systems by roof, wall, and roof/wall were designed. The optimal green systems were determined from more than 51 billion possible scenarios. The model can be used as a decision making tool for the green systems' implementation. Abstract: The green systems ensured a green space, improved the thermal comfort of the residents by making the seasonal indoor temperature pleasant, and saved energy in buildings. This study aimed to develop an optimization model for the optimal green systems by considering the thermal comfort in and energy consumption of an educational facility. In addition, the optimal design scenarios were analyzed considering their economic and environmental effects. The study was conducted as follows: (i) selection of the design variables and objective function; (ii) optimization of the green systems; (iii) comparative analysis of the standard and optimal designs; and (iv) economic and environmental assessment of the optimal design scenarios. In order to compare the thermal comfort of the green systems with that of the existing building, this study used the percentage of predicted dissatisfied (PPD) which is the thermal comfort index based on Fanger's model. The implementation of the green systems improved the thermal comfort by 0.18–2.18% in terms of PPD, and reduced the energy consumption by 0.02–11.00%. The economic and environmental effects of the optimal green systems also showed up to 12.62% and 18.36% reductions, respectively. Thus, the implementation of the green systems was effective in terms of thermal comfort, energy consumption, life cycle cost, and life cycle assessment. This study could help the potential green systems users establish the optimal green systems in terms of thermal comfort, energy consumption, and the economic and environmental effects.